2002
DOI: 10.1016/s0301-7516(01)00064-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flotation frothers on bubble size and foam stability

Abstract: In presenting this thesis in partial fulfilment of the requirements for an advanced degree at the University of British Columbia, I agree that the Library shall make it freely available for reference and study. I further agree that permission for extensive copying of this thesis for scholarly purposes may be granted by the head of my department or by his or her representatives. It is understood that copying or publication of this thesis for financial gain shall not be allowed without my written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
0
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(187 citation statements)
references
References 39 publications
7
152
0
15
Order By: Relevance
“…The observation also raises a fundamental question. The CCC concept implies frother is involved only in preserving the bubble size produced by the machine; i.e., the machine produces, frother preserves hypothesis [10,35]. This argument means that D L is the machine-produced Sauter mean size and might be expected to be invariant for given machine operating conditions but Figure 13 argues that frothers play some role in the initial bubble creation size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation also raises a fundamental question. The CCC concept implies frother is involved only in preserving the bubble size produced by the machine; i.e., the machine produces, frother preserves hypothesis [10,35]. This argument means that D L is the machine-produced Sauter mean size and might be expected to be invariant for given machine operating conditions but Figure 13 argues that frothers play some role in the initial bubble creation size.…”
Section: Discussionmentioning
confidence: 99%
“…This action is usually ascribed to frothers acting to reduce coalescence [9]. Combining these points Cho and Laskowski [10] introduced the term critical coalescence concentration (CCC) to describe the minimum concentration giving the minimum bubble size. Laskowski [11] showed that all frothers produced a similar D 32 -C trend, differing only in their CCC, for example DowFroth 250 with CCC 9.1 ppm and MIBC 11.2 ppm.…”
Section: Critical Coalescence Concentration and Hydrophile-lipophilementioning
confidence: 99%
“…15 m/s) line by determining the 95% confidence interval of the line [1]. This graphical method is similar to that used in determining the critical micelle concentration (CMC) from a surface tension-concentration plot [23] and the critical coalescence concentration (CCC) from a bubble size-concentration plot [4,18]. A more practical approach is to use a formula, which allows one to rapidly and accurately determine the CMV of frothers.…”
Section: Terminal Bubble Velocitymentioning
confidence: 99%
“…This influence has to be experimentally determined in terms of the most efficient range of concentrations, where desired liquid/gas interface properties, triggering useful frothers' features and allowing their classification, can be achieved. The experimentally determined parameters, which are commonly used for these purposes, are for example, the concentration at the minimum bubble velocity (CMV) [1][2][3], the critical coalescence concentration (CCC) [4][5][6], the concentration at half of the maximum foam height (CMH) [7] or the dynamic frothability index (DFI) [8][9][10]. Since all these parameters depend mainly on the properties of the liquid/gas interface, the corresponding characteristic frother concentration values can vary strongly, depending on the frother's family (type) and carbon chain length.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling gas flow rate (if possible) 2. Optimize frother consumption by ensuring that the plant never operates above the critical coalescence concentration, or CCC, (Cho and Laskowski, 2002) for the given plant conditions.…”
Section: Process Control Strategiesmentioning
confidence: 99%